Arthroscopic Coracoid Transfer in the Lateral Decubitus Position is Safe and Effective at Short-Term Follow-Up - Varun Singla, M.D; Michael B. Banffy, M.D (Elsevier, 2024)
Purpose: To report on operative and clinical outcomes in a series of shoulders treated with arthroscopic Latarjet performed in the lateral decubitus position. Methods: Patients with shoulders that underwent arthroscopic Latarjet in the lateral decubitus position were identified. Data were retrospectively collected, including patient demographics, operative times, intra- and postoperative complications, and clinical and functional outcomes. Descriptive statistics were performed. Results: Eighteen shoulders in 17 patients were included in the study with a mean follow-up of 14 ± 12.1 months (range, 4-39 months). The mean operative time for all procedures was 132.2 ± 18.0 minutes, and the mean operative time for the first half of the cohort was significantly longer than that of the second half (141.6 ± 14.2 minutes vs 122.8 ± 17.0 minutes, P = .02). There were no intraoperative complications, and no patients required a conversion to open surgery. One patient experienced a recurrent dislocation after a traumatic event but was able to be treated nonoperatively. Preoperative and postoperative patient-reported outcome measures (PROMs) were able to be collected on 8 of 18 patients (44.4%). Although all PROMs demonstrated improvements postoperatively, only the Single Assessment Numeric Evaluation score and American Shoulder and Elbow Surgeons Shoulder Index displayed a statistically significant increase (P < .05). Five of 8 (62.5%) shoulders demonstrated bony fusion on postoperative computed tomography scan. Of those eligible, 100% of patients returned to sport or felt that they could return if they wanted to. Conclusions: The arthroscopic Latarjet is an effective procedure for managing glenohumeral instability and can safely be performed in the lateral decubitus position. Level of Evidence: Level IV, therapeutic case series.